Neuroendocrine regulation of female aggression - Oliveira, Vinícius Elias de Moura; Bakker, Julie (Frontiers in Endocrinology, 2022)
Classically the neurobiology of aggression has been studied exclusively in males. Thus, by default, females have been considered mildly aggressive except during lactation. Interestingly, recent studies in rodents and humans have revealed that non-lactating females are able to show exacerbated and pathological aggression similarly to males. This review provides an overview of recent findings on the neuroendocrine mechanisms regulating aggressive behavior in females. In particular, the focus will be on novel rodent models of exaggerated aggression established in non-lactating females. Among the neuromodulatory systems influencing female aggression, special attention has been given to sex-steroids and sex-steroid-sensitive neuronal populations (i.e., the core nuclei of the neural pathway of aggression) as well as to the neuropeptides oxytocin and vasopressin which are major players in the regulation of social behaviors.